Breast Cancer Risk Reduction and Early Detection - Sauter, Edward R.; Daly, Mary B.; SpringerLink (Online service) (Boston, MA : Springer US, 2010)
Breast Cancer Risk Reduction and Early Detection provides an in-depth overview of the factors of breast cancer risk and what health care providers and individuals can do to impact the risk of breast cancer in their patient or themselves. Many books address breast cancer in general or focus on treatment; few focus on prevention and early detection, including current practices and new strategies in: epidemiology, primary prevention, chemoprevention, surgical prevention, breast specific (physical examination, imaging, intraductal) and systemic screening and early detection. Written by experts in their fields, this book is a resource to researchers, clinicians and the broad group of health care providers. It is a source of accurate information for individuals to use to reduce risk of new or recurrent breast cancer and to apply best practices for early detection.
I: PREVENTION -- Risk Factors -- Lifestyle Factors and Risk of Breast Cancer: A Review of Randomized Trial Findings -- Breast Cancer Chemoprevention -- Surgical Management of Inherited Susceptibility to Breast Cancer -- II: EARLY DETECTION -- Clinical Breast Examination and Breast Self-Examination -- Mammography -- Current Status and Future Prospects in Breast Carcinoma of Positron Emission Tomography -- Breast MRI -- Genetic and Molecular Approaches to Imaging Breast Cancer -- Intraductal Approaches: Nipple Aspirate Fluid to Assist in Breast Cancer Detection -- Intraductal Approaches: Mammary Ductoscopy and Ductal Lavage to Assist in the Diagnosis of Breast Cancer -- Blood Markers -- Circulating Tumor Cells in Breast Cancer.
Keywords: Medicine; Oncology; Radiology, Medical; Cancer -- Surgery; Medicine & Public Health; Oncology; Surgical Oncology; Cancer Research; Imaging / Radiology; Public Health/Gesundheitswesen.